(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article discusses the importance of supervised learning and how it is widely used today. In addition, information was provided on the types of Supervised Learning, such as Classification and Regression, and the advantages and disadvantages of this learning. In addition, the importance of this training in the work of modern technologies is explained.